ANALYSIS OF THE EFFECT OF STANDARD OPERATIONAL PROCEDURES, INTERNAL SUPERVISION ON EMPLOYEE PERFORMANCE AT THE REGIONAL TAX AND LEVEL MANAGEMENT AGENCY OF TAPIN DISTRICT IN RANTAU - Abdul Kadir (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2021)
Human resources are one of the implementing elements in organizational activities that are tasked and responsible for carrying out organizational operational activities. In carrying out the duties of an employee, perseverance in work is needed, agile, has the expertise and ability to carry out tasks. In an organization to be able to develop and progress, it really depends on the performance of the personnel themselves. This research is to find out the Analysis of the Effect of Standard Operating Procedures, Internal Controls and Workloads on Employee Performance at the Regional Tax and Levy Management Agency of Tapin Regency in Rantau. The research method used is analytic survey. The type of research is explanatory research. A sample of 37 people used total sampling technique. Data collection techniques used questionnaires, documentation, interviews and observations. Validity and reliability tests were carried out on the research instrument. Data were analyzed by multiple linear regression analysis with classical assumption test. The results showed that Standard Operating Procedures, Internal Control and Workload had a significant simultaneous effect on Employee Performance at the Regional Tax and Levy Management Agency of Tapin Regency in Rantau. Standard Operating Procedures and Internal Controls have a significant partial effect on Employee Performance at the Tapin Regency Regional Tax and Retribution Management Agency in Rantau and there is no significant effect of Workload on Employee Performance at the Tapin Regency Regional Tax and Levies Management Agency in Rantau. Standard Operating Procedures have a dominant and significant effect on employee performance at the Regional Tax and Levy Management Agency of Tapin Regency in Rantau